Trade unions in crisis : the 1961 ETU ballot-rigging scandal. - Communist Party of Great Britain; Archive Trust of the Communist Party of Great Britain (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2020)
The ETU ballot-rigging trial was a case brought to the High Court by prominent union members John Thomas Byrne and Frank Chapple in 1961. They alleged that members of the Communist Party of Great Britain (CPGB) had engaged in "a conspiracy to defraud" in the most recent elections of the Electrical Trades Union (ETU), a relatively successful body that represented electricians, wire fitters, and telephone engineers. The judge ultimately ruled in the plaintiffs' favour. This collection contains verbatim transcripts of the court case. The transcripts provide a unique insight into the CPGB’s influence in the post-war trade union movement.
Date range: 1961.
Keywords: Electrical Trades Union (Great Britain) -- History -- Sources; Labor unions -- Great Britain -- History -- 20th century -- Sources; Elections -- Corrupt practices; Communism -- Great Britain -- History -- 19th century -- Sources